SIMULASI PENGARUH ORIENTASI SUDUT SERAT TERHADAP TEGANGAN TARIK LAMINATED COMPOSITE - Hilmi Iman Firmansyah; Sulistyono Sulistyono; Hangga Wicaksono (Polinema Press, Politeknik Negeri Malang, 2021)
Composite is a material consisting of a mixture or combination of two or more materials, either micro or macro, where the properties of the material are different in shape and chemical composition from the original substance. In this study, the composite was tested to determine the tensile strength using simulation. Composite material modeling consists of carbon fiber as reinforcement and epoxy resin as the matrix. Then the composite material was given a uniaxial loading with a loading value of 50 N. By using variations in the orientation of the fiber angle 45ᵒ/90ᵒ/-45ᵒ, 45ᵒ/90ᵒ/-45ᵒ and 60ᵒ/45ᵒ/-60ᵒ. This study aimed to determine the effect of fiber angle orientation on tensile strength, maximum deformation and location of maximum stress on carbon fiber composites. The best composite design is the composite with fiber angle orientation of 45ᵒ/90ᵒ/-45ᵒ with a tensile stress value of 3.6 MPa and the smallest deformation of 0.0644 mm.